The acquisition, analyses and interpretation of fMRI data: a study on functional specialisation in primary auditory cortices - Yusoff AN; Abdul Hamid K; Mohamad M; Abd Hamid AI (Penerbit UKM, 2008)
In this study, functional magnetic resonance imaging (fMRI) is used to investigate func-tional specialisation in human auditory cortices during listening. A silent fMRI paradigm was used to reduce the scanner sound artefacts on functional images. The subject was instructed to pay attention to the white noise stimulus binaurally given at an inten-sity level of 70 dB higher than the hearing level for normal people. Functional speciali-sation was studied using the Matlab-based Statistical Parametric Mapping (SPM5) software by means of fixed effects (FFX), random effects (RFX) and conjunction analyses. Individual analyses on all subjects indicated asymmetrical bilateral activation of the left and right hemispheres in Brodmann areas (BA) 22, 41 and 42, involving the primary and secondary auditory cortices. The percentage of signal change is larger in the BA22, 41 and 42 on the right as compared to the ones on the left (p>0.05). The average number of activated voxels in all the respective Brodmann areas are higher in the right hemisphere than in the left (p>0.05). FFX results showed that the point of maximum intensity was in the right BA41 whereby 599±1 activated voxels were ob-served in the right temporal lobe as compared to 485±1 in the left temporal lobe. The RFX results were consistent with that of FFX. The analysis of conjunction which fol-lowed, showed that the right BA41 and left BA22 as the common activated areas in all subjects. The results confirmed the specialisation of the right auditory cortices in pro-cessing non verbal stimuli